Performance-Based Comparison of Neonatal Intubation Training Outcomes. (February 2015) - Andreatta, Pamela B.; Klotz, Jessica J.; Dooley-Hash, Suzanne L.; Hauptman, Joe G.; Biddinger, Bea; House, Joseph B.; Ahern, Kathy
<x xml:space="preserve">Abstract</x> The purpose of this article was to establish psychometric validity evidence for competency assessment instruments and to evaluate the impact of 2 forms of training on the abilities of clinicians to perform neonatal intubation. To inform the development of assessment instruments, we conducted comprehensive task analyses including each performance domain associated with neonatal intubation. Expert review confirmed content validity. Construct validity was established using the instruments to differentiate between the intubation performance abilities of practitioners (N = 294) with variable experience (novice through expert). Training outcomes were evaluated using a quasi-experimental design to evaluate performance differences between 294 subjects randomly assigned to 1 of 2 training groups. The training intervention followed American Heart Association Pediatric Advanced Life Support and Neonatal Resuscitation Program protocols with hands-on practice using either (1) live feline or (2) simulated feline models. Performance assessment data were captured before and directly following the training. All data were analyzed using analysis of variance with repeated measures and statistical significance set at P < .05. Content validity, reliability, and consistency evidence were established for each assessment instrument. Construct validity for each assessment instrument was supported by significantly higher scores for subjects with greater levels of experience, as compared with those with less experience (P = .000). Overall, subjects performed significantly better in each assessment domain, following the training intervention (P = .000). After controlling for experience level, there were no significant differences among the cognitive, performance, and self-efficacy outcomes between clinicians trained with live animal model or simulator model. Analysis of retention scores showed that simulator trained subjects had significantly higher performance scores after 18 weeks (P = .01) and 52 weeks (P = .001) and cognitive scores after 52 weeks (P = .001). The results of this study demonstrate the feasibility of using valid, reliable assessment instruments to assess clinician competency and self-efficacy in the performance of neonatal intubation. We demonstrated the relative equivalency of live animal and simulation-based models as tools to support acquisition of neonatal intubation skills. Retention of performance abilities was greater for subjects trained using the simulator, likely because it afforded greater opportunity for repeated practice. Outcomes in each assessment area were influenced by the previous intubation experience of participants. This suggests that neonatal intubation training programs could be tailored to the level of provider experience to make efficient use of time and educational resources. Future research focusing on the uses of assessment in the applied clinical environment, as well as identification of optimal training cycles for performance retention, is merited.